Prevalence of tuberculosis in adolescents, western Kenya: implications for control programs. (June 2015) - Nduba, Videlis; Hoog, Anna H. Van't; Mitchell, Ellen; Onyango, Peter; Laserson, Kayla; Borgdorff, Martien
Highlights: We enrolled adolescents to determine the prevalence of tuberculosis. We found a high prevalence of TB among adolescents not explained by HIV. We found a high burden of non-tuberculous mycobacteria, thus value of speciation. There is a need to improve case detection among adolescents, e.g., with Xpert MTB/RIF. Summary: Objective: The aim of this study was to determine the prevalence of tuberculosis (TB) in adolescents in western Kenya. Methods: A cohort study of 5004 adolescents aged 12–18 years was conducted. Adolescents were screened for prevalent TB using clinical criteria, history of TB contact, and a Mantoux test. Cases of suspected TB were investigated through two sputum examinations (microscopy and liquid culture) and chest radiography. Results: Out of 5004 adolescents enrolled, 1960 (39.2%) were identified with suspected TB, including 1544 with a positive Mantoux (prevalence 1544/4808, 32.1%), 515 with symptoms suggestive of TB (10.3%), and 144 (2.9%) with household TB contact. Sixteen culture-confirmed (definite) and 18 probable pulmonary TB (PTB) cases were identified, reflecting a prevalence estimate of 3.2/1000 (definite) and 6.8/1000 all PTB, respectively. Only one smear-positive case was detected. The case notification rate among 12–18-year-old adolescents for all TB was 101/100 000, yielding a patient diagnostic rate of 0.13 (95% confidence interval 0.03–3.7) cases detected per person-year for all TB. Conclusion: The prevalence of PTB among adolescents is high, with the majority of cases not detected routinely. Innovative active case finding including the wider use of Xpert MTB/RIF is needed to detect smear-negative TB among adolescents.